2021
DOI: 10.3390/su132413863
|View full text |Cite
|
Sign up to set email alerts
|

People or Systems: Does Productivity Enhancement Matter More than Energy Management in LEED Certified Buildings?

Abstract: This study examines the impact of energy management and productivity-enhancing measures, implemented as part of LEED Existing Buildings Operations and Management (EBOM) certification, on source energy use intensity and rental premiums of office spaces using data on four major US markets. Energy management practices, comprised of commissioning and advanced metering, may reduce energy usage. Conversely, improving air quality and occupant comfort in an effort to increase worker productivity may in turn lead to hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 65 publications
0
1
0
Order By: Relevance
“…Furthermore, the long-term benefit is even greater when the performance gap between design and reality is reduced. For example, it has been shown that LEED's Existing Building Operation and Management can successfully achieve this gap reduction [17].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the long-term benefit is even greater when the performance gap between design and reality is reduced. For example, it has been shown that LEED's Existing Building Operation and Management can successfully achieve this gap reduction [17].…”
Section: Introductionmentioning
confidence: 99%